2006
DOI: 10.1016/s1808-8694(15)30996-4
|View full text |Cite
|
Sign up to set email alerts
|

Is there a reason for performing frontal sinus trephination at 1 cm from midline? A tomographic study.

Abstract: Analyzing the results, the trephination may be performed at variable points of the frontal sinus, but the distance of 1 cm from midline appears to be safer and shows better aesthetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Piltcher et al reviewed 69 CT scans similarly at measurements of 5 mm, 10 mm, and 15 mm from midline. Men presented a frontal sinus significantly larger in the distances of 5 mm and 10 mm when compared to women, but there was no statistical difference in the depth of the sinus at 15 mm . The frontal sinus depth measured at 5 mm of the midline was significantly larger than that at 10 and 15 mm, just as the measure at 10 mm was significantly higher when compared to that at 15 mm (12.22 vs. 11.78 mm, 12.22 mm vs. 10.78 mm, 11.78 mm vs. 10.78 mm) .…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…Piltcher et al reviewed 69 CT scans similarly at measurements of 5 mm, 10 mm, and 15 mm from midline. Men presented a frontal sinus significantly larger in the distances of 5 mm and 10 mm when compared to women, but there was no statistical difference in the depth of the sinus at 15 mm . The frontal sinus depth measured at 5 mm of the midline was significantly larger than that at 10 and 15 mm, just as the measure at 10 mm was significantly higher when compared to that at 15 mm (12.22 vs. 11.78 mm, 12.22 mm vs. 10.78 mm, 11.78 mm vs. 10.78 mm) .…”
Section: Resultsmentioning
confidence: 74%
“…Men presented a frontal sinus significantly larger in the distances of 5 mm and 10 mm when compared to women, but there was no statistical difference in the depth of the sinus at 15 mm. 33 The frontal sinus depth measured at 5 mm of the midline was significantly larger than that at 10 and 15 mm, just as the measure at 10 mm was significantly higher when compared to that at 15 mm (12.22 vs. 11.78 mm, 12.22 mm vs. 10.78 mm, 11.78 mm vs. 10.78 mm). 33 In their study, the sinus depth when measured at 5, 10, and 15 mm away from the midline showed statistically significant differences, demonstrating that the closer the proximity to the midline, the deeper it was.…”
Section: Systematic Reviewmentioning
confidence: 81%
See 3 more Smart Citations